Antibacterial Activity of Extract and Fraction From Shitake Mushroom (Lentinula edodes) Against Acne Bacteria - Sukmawati, Ika Kurnia; Yuniarto, Ari; Alighita, Widhya; Zam-zam J, Ade (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Acne is an inflammatory disease that occurs in the skin triggered by the bacteria acne treatment can be done by using natural materials that shiitake mushrooms (Lentinus edodes). This aims of this study were to determining the antibacterial activity of extracts and fractions shiitake mushrooms with broth microdilution method, determining the value of equality shiitake mushrooms with antibacterial comparison and determining the morphological changes of bacteria after exposure to the test sample with a Scanning Electron Microscope (SEM). Tests conducted antibacterial activity against Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus at concentrations used is 1 ppm, 2 ppm, 4 ppm, 8 ppm, 16 ppm, 32 ppm, 64 ppm, 128 ppm, 256 ppm, 512 ppm. Best MIC value obtained in fraction of ethyl acetate and n-hexane fraction of the bacterium Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus at a concentration of 256 ppm. KBM value of the n-hexane fraction against Staphylococus aureus bacteria at concentrations of 512 ppm and ethyl acetate fraction against bacteria Staphylococus aureus and epidermidis at a concentration of 512 ppm. Value equality is obtained 1 mg of ethyl acetate fraction of shiitake mushrooms equivalent to 5.346 x 10-2 mg of tetracycline. SEM test results showed the presence of antibacterial activity which is indicated by a change in cell morphology, their lumps and their cell wall frown on Propionibacterium acnes were exposed to ethyl acetate fraction.Key words: Acne, Lentinus edodes, antibacterials, microdilution, SEM